2019
DOI: 10.1002/aoc.5102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, antioxidant and anti‐diabetic activities of a novel protein–vanadium complex

Abstract: The protein–vanadium complex was successfully synthesized and systematically characterized using electron paramagnetic resonance, Fourier transform‐infrared spectroscopy and thermogravimetric analysis. The antioxidant activity analysis indicated that it had better radical scavenging activity on 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH), 2,2′‐azinobis (3‐ethylbenzothiazoline)‐6‐sulfonic acid (ABTS) and O2− compared with the free protein and vanadate. Additionally, the complex exhibited high anti‐diabetic activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…Our previous work showed that the synthetic V-P complex had high antidiabetic activity in vitro [24]. Here, the effect of different concentration of V-P complexes on the human preadipocyte differentiation was determined.…”
Section: Effect Of V-p Complex On Lipid Accumulationmentioning
confidence: 93%
See 4 more Smart Citations
“…Our previous work showed that the synthetic V-P complex had high antidiabetic activity in vitro [24]. Here, the effect of different concentration of V-P complexes on the human preadipocyte differentiation was determined.…”
Section: Effect Of V-p Complex On Lipid Accumulationmentioning
confidence: 93%
“…Additionally, our previous study showed that the synthetic vanadium-protein complex had antidiabetic activity in vitro [24]. It has been demonstrated that vanadium complexes with proper organic ligands can enhance vanadium's liposoluble properties, promote gastrointestinal absorption, tissue uptake and reduce the toxicity of the vanadium [25].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations